Importance of Protease Inhibition in Studies on Purified Factor VIII (Antihaemophilic Factor) - Beck, Eugen A.; Bachmann, Peter; Barbier, Peter; Furlan, Miha (Thrombosis and Haemostasis, 1976)
According to some authors factor VIII procoagulant activity may be dissociable from carrier protein (MW~ 2 × 106) by agarose gel filtration, e.g. at high ionic strength. We were able to reproduce this phenomenon. However, addition of protease inhibitor (Trasylol) prevented the appearance of low molecular weight peak of factor VIII procoagulant activity both at high ionic strength and elevated temperature (37°C). We conclude from our results that procoagulant activity and carrier protein (von Willebrand factor, factor VIII antigen) are closely associated functional sites of native factor VIII macro molecule. Consequently, proteolytic degradation should be avoided in functional and structural studies on factor VIII and especially in preparing factor VIII concentrate for therapeutic use.